Distance-constrained grid colouring - Aszalós László; Bakó Mária (Acta Universitatis Sapientiae: Informatica, 2016)
Distance-constrained colouring is a mathematical model of the frequency assignment problem. This colouring can be treated as an optimization problem so we can use the toolbar of the optimization to solve concrete problems. In this paper, we show performance of distance-constrained grid colouring for two methods which are good in map colouring.